Diet-altered body temperature rhythms are associated with altered rhythms of clock gene expression in peripheral tissues in vivo. (August 2021) - Goh, Grace H.; Mark, Peter J.; Blache, Dominique; Binks, Daniel; Parsons, Rex; Rawashdeh, Oliver; Maloney, Shane K.
Abstract: Temperature rhythms can act as potent signals for the modulation of the amplitude and phase of clock gene expression in peripheral organs in vitro, but the relevance of the circadian rhythm of core body temperature (Tc ) as a modulating signal in vivo has not yet been investigated . Using calorie restriction and cafeteria feeding, we induced a larger and a dampened Tc amplitude, respectively, in male Wistar rats, and investigated the circadian expression profile of the core clock genes Bmal1, Per2, Cry1, and Rev-erbα, the heat-responsive genes heat shock protein 90 ( Hsp90 ) and cold-inducible RNA binding protein ( Cirbp ), and Pgc1α, Pparα/γ/δ, Glut1/4, and Chop10 in the liver, skeletal muscle, white adipose tissue (WAT), and adrenal glands. Diet-altered Tc rhythms differentially affected the profiles of clock genes, Hsp90, and Cirbp expression in peripheral tissues. Greater Tc amplitudes elicited by calorie restriction were associated with large amplitudes of Hsp90 and Cirbp expression in the liver and WAT, in which larger amplitudes of clock gene expression were also observed. The amplitudes of metabolic gene expression were greater in the WAT, but not in the liver, in calorie-restricted rats. Conversely, diet-altered Tc rhythms were not translated to distinct changes in the amplitude of Hsp90, Cirbp, or clock or metabolic genes in the skeletal muscle or adrenal glands. While it was not possible to disentangle the effects of diet and temperature in this model, taken together with previous in vitro studies, our study presents novel data consistent with the notion that the circadian Tc rhythm can modulate the amplitude of circadian gene expression in vivo. The different responses of Hsp90 and Cirbp in peripheral tissues may be linked to the tissue-specific responses of peripheral clocks to diet and/or body temperature rhythms, but the association with the amplitude of metabolic gene expression is limited to the WAT. Highlights: Energy balance affects the rhythm of body temperature (Tc ) in vivo . Amplitude of Hsp90 and Cirbp are associated with Tc amplitude in fat tissue and liver. Amplitude of clock gene expression in fat, but not liver, are also altered by Tc . Hsp90, Cirbp, and clock genes are unaffected by Tc in muscle and adrenal tissue.